Application of Traditional Graphic Elements Based on Fiber Bragg Grating Tactile Sensor Technology - Jing Xu (Hindawi Limited, 2021)
In today’s era, sensing technology has been very developed in the fields of machinery, medicine, safety monitoring, and so on. In order to be applicable to more fields, new sensing technologies are also evolving. Tactile and sensory states are two important indicators of human induction to external things. Based on the contact force information between fiber Bragg grating tactile sensor and human body, this paper uses a new fiber Bragg grating tactile sensing system to study the artistic elements of ink painting in modern graphic design. Subsequently, the structure and specific performances of the sensor experimental data are analyzed. With its small volume, low cost, high sensitivity, and good compatibility with the observed body, the new fiber Bragg grating tactile sensor will not be affected by external electromagnetic interference, various noise signals, complex integration, and other problems. According to the data observed by ink painters in this paper, the new tactile sensing technology of fiber Bragg grating can well control the external interference factors. In general, the technology is of great social and practical value.